Shifting Motives : Explaining the Buildup in official Reserves in Emerging Markets Since the 1980's - Ghosh, Atish (IMF Working Papers; Working Paper, 2012)
Why have emerging market economies (EMEs) been stockpiling international reserves? We find that motives have varied over time?vulnerability to current account shocks was relatively important in the 1980s but, as EMEs have become more financially integrated, factors related to the magnitude of potential capital outflows have gained in importance. Reserve accumulation as a by-product of undervalued currencies has also become more important since the Asian crisis. Correspondingly, using quantile regressions, we find that the reason for holding reserves varies according to the country's position in the global reserves distribution. High reserve holders, who tend to be more financially integrated, are motivated by insurance against capital account rather than current account shocks, and are more sensitive to the cost of holding reserves than are low-reserve holders. Currency undervaluation is a significant determinant across the reserves distribution, albeit for different reasons.